Gamification to Engage Young Learners in the English Class - Barbosa Alfonso, Luisa Fernanda; Dueñez Castro, Juliana; Patiño Flórez, Diana; Castellanos Jaimes , Judith (Universidad Pedagógica y Tecnológica de Colombia, 2022)
In this action research, our purpose was to carry out a pedagogical intervention in the English class using the Gamification method with first grade children in a private bilingual school. In the needs analysis we identify aspects that emerge from learning such as lack of motivation or disinterest and low development in listening and speaking skills. The study is based on the questions, How does gamification support children's English skills? And What is the role of gamification in student engagement? We focus on three theoretical constructs: significant learning, young learners and gamification, taking into account authors such as Rieber (1996); Delgado and Breña, (2022), Ospina (2006), among others. When analyzing field notes and video transcripts, the results show that there was active participation, continuous student learning, greater interest in exploring, and confidence to ask unknown topics without fear. The development of listening and speaking skills was evidenced when recognizing, pronouncing and associating meanings in English and Spanish. The children expressed their knowledge, worked as a team with their peers, and there was commitment from the students